Intranasal Delivery of Targeted Nanoparticles Loaded With miR-132 to Brain for the Treatment of Neurodegenerative Diseases - Su, Yu; Sun, Bixi; Gao, Xiaoshu; Dong, Xinyue; Fu, Lanbo; Zhang, Yingxin; Li, Zhulin; Wang, Yue; Jiang, Hongyu; Han, Bing (Frontiers in Pharmacology, 2020)
Abstract: Effective treatments for neurodegenerative diseases need to be developed.MiR132 is abundantly expressed in the brain, and it modulates neuron morphology and plays a key role in maintaining neuron survival. Regulating miR132 can effectively improve the symptoms of Alzheimer's disease. It can also reduce cell death after cerebral hemorrhage, improve the microenvironment of hematoma lesions and provide a certain protective effect from brain damage after cerebral ischemia. MiR132 has great potential in the treatment of cerebral ischemia and Alzheimer's disease. To prevent the degradation of miR132 in the blood, we used mouse and rat models of Alzheimer's disease with ischemic brain injury, and we delivered Wheat germ agglutinin (WGA)-NPs-miR132 intranasally to treat neurological damage after cerebral ischemia. Synaptic protein expression levels in Alzheimer's mouse models increased significantly after administration. Thus, nasal delivery of WGA-NPs-miR132 could be a novel approach for treating neurodegenerative diseases.